In the eye of a leader: Eye-directed gazing shapes perceptions of leaders' charisma - Maran, Thomas; Furtner, Marco; Liegl, Simon; Kraus, Sascha; Sachse, Pierre (The Leadership quarterly, 2019)
Charismatic leadership improves organizational performance. Charisma itself can be defined as a repertoire of behaviors designed to communicate, however its constituents remain elusive. We hypothesized leaders' eye-directed gaze to be one such behavior, and therefore linked to their charisma. Using eye-tracking, we monitored gaze during a simulated leadership scenario, in which subjects attempted to influence followers towards a common goal. In two studies, we found subjects' impressions of their own charisma to predict the frequency and duration of gaze directed at their followers' eyes. In addition, longer and more frequent eye-directed gazing led leaders to appear both more charismatic and prototypical of their position in the eyes of their audience. Our findings provide first evidence that leaders' gazing towards the eyes of an audience is linked to their charisma. By investigating a leader's charisma through the lens of the signaling approach, we offer insight into the behaviors constituting charismatic leadership. •Leaders' charisma is composed of a repertoire of communicative behaviors.•Leaders' gaze behavior was monitored during a simulated leadership scenario.•Eye-directed gazing is predicted by leaders' impressions of their own charisma.•Eye-directed gazing shapes observers' perceptions of leaders, increasing ascribed charisma and leader prototypicality.